Expenditure on education and physical culture in the commune of Skulsk and Wilczyn in 2015-2018. Comparative analysis - Karczewska, Wiktoria (Journal of Education, Health and Sport, 2021)
According to the Constitution of the Republic of Poland of 1997, a commune is the basic unit of local self-government. The commune realizes its own tasks and commissioned tasks, and its aim is cater to local residents needs. In both analyzed communes, the main source of expenditure were own tasks. In the balance sheet, the education department had the biggest share in the expenditure of both communes. In particular, these are expenses for kindergartens, primary schools, lower secondary schools and teachers’ salaries. Expenditure on physical culture does not significantly affect the balance sheet of communes.